2017
DOI: 10.1093/mnras/stx1561
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Compton-thick AGN candidates at z > 2 with Chandra using the >8 keV rest-frame spectral curvature

Abstract: To fully understand cosmic black hole growth we need to constrain the population of heavily obscured active galactic nuclei (AGN) at the peak of cosmic black hole growth (z ∼1-3). Sources with obscuring column densities higher than 10 24 atoms cm −2 , called Compton-thick (CT) AGN, can be identified by excess X-ray emission at ∼ 20-30 keV, called the "Compton hump". We apply the recently developed Spectral Curvature (SC) method to high-redshift AGN (2 < z < 5) detected with Chandra. This method parametrizes th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Yet again, the heavily absorbed AGNs generally occupy the same parameter space as unobscured AGNs. The spectral curvature method (Koss et al 2016) may provide a more effective means of selecting heavily AGNs at higher redshift in the XXL-N field, and indeed, Baronchelli et al (2017) demonstrated its effectiveness in selecting high-redshift (z > 2) CT AGNs in both the Chandra Deep Field South and the Chandra COSMOS legacy survey.…”
Section: Diagnosis Of N H In the Xmm Xxl Fieldmentioning
confidence: 99%
“…Yet again, the heavily absorbed AGNs generally occupy the same parameter space as unobscured AGNs. The spectral curvature method (Koss et al 2016) may provide a more effective means of selecting heavily AGNs at higher redshift in the XXL-N field, and indeed, Baronchelli et al (2017) demonstrated its effectiveness in selecting high-redshift (z > 2) CT AGNs in both the Chandra Deep Field South and the Chandra COSMOS legacy survey.…”
Section: Diagnosis Of N H In the Xmm Xxl Fieldmentioning
confidence: 99%
“…At these high column densities, the attenuation of X-rays is mainly due to Compton-scattering rather than photoelectric absorption; these sources are the so-called "Compton-thick" (CT) AGNs (N H 1.5 × 10 24 cm −2 ), of which only a few have been identified in the local Universe (Burlon et al 2011;Ricci et al 2015, and references therein). At higher redshifts, hundreds of CT AGN candidates have been identified in X-rays thanks to XMM and Chandra observations at E<10 keV (e.g., Comastri et al 2011;Feruglio et al 2011;Brightman et al 2014;Buchner et al 2015;Baronchelli et al 2017) and NuSTAR data at higher X-ray energies (e.g., Civano et al 2015;Mullaney et al 2015;Lansbury et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Koss et al (2016) developed an SC analysis technique that uses weighted averages of different energy bands above 10 keV to estimate the Compton thickness of an AGN. For CT AGN, the SC value calculated is SC CT ≥ 0.4 (Koss et al 2016;Baronchelli et al 2017). We applied this technique to the two AGNs in our sample that are detected at E > 10 keV, i.e.…”
Section: Discussionmentioning
confidence: 99%